Antibodies to heteromeric glycolipid complexes in multifocal motor neuropathy - Galban-Horcajo, F; Fitzpatrick, A; Hutton, A; Dunn, S; Kalna, G; Brennan, K; Rinaldi, S; Yu, R; Goodyear, C; Willison, H (2013)
Background: Measurement of anti-GM1 IgM antibodies in multifocal motor neuropathy (MMN) sera is confounded by relatively low sensitivity that limits clinical usefulness. Combinatorial assay methods, in which antibodies react to heteromeric complexes of two or more glycolipids, are being increasingly applied to this area of diagnostic testing. Methods: A newly developed combinatorial glycoarray able to identify antibodies to 45 different heteromeric glycolipid complexes and their 10 individual glycolipid components was applied to a randomly selected population of 33 MMN cases and 57 normal or disease controls. Comparison with an enzyme-linked immunosorbent assay (ELISA) was conducted for selected single glycolipids and their complexes. Results: By ELISA, 22/33 MMN cases had detectable anti-GM1 IgM antibodies, whereas 19/33 MMN samples were positive for anti-GM1 antibodies by glycoarray. Analysis of variance (anova) revealed that of the 55 possible single glycolipids and their 1:1 complexes, antibodies to the GM1:galactocerebroside (GM1:GalC) complex were most significantly associated with MMN, returning 33/33 MMN samples as positive by glycoarray and 29/33 positive by ELISA. Regression analysis revealed a high correlation in absolute values between ELISA and glycoarray. Receiver operator characteristic analysis revealed insignificantly different diagnostic performance between the two methods. However, the glycoarray appeared to offer slightly improved sensitivity by identifying antibodies in four ELISA-negative samples. Conclusions: The use of combinatorial glycoarray or ELISA increased the diagnostic sensitivity of anti-glycolipid antibody testing in this cohort of MMN cases, without significantly affecting specificity, and may be a useful assay modification for routine clinical screening. © 2012 The Author(s) European Journal of Neurology © 2012 EFNS.